On the Prediction of the Design Criteria for Modification of Contact Stresses Due To Thermal Stresses in the Gear Mesh - Atan, Ebubekir (Elsevier Ltd., 2005)
The mechanism of surface failure due to temperature rise is a very important problem in gear design. Thermal considerations have received considerable attention from the gear researchers but only for scoring failures when the destruction of lubrication film occurs as a result of temperature rise. In spite of the wealth of literature on this subject, this problem is not fully analyzed. The objectives of this paper are to consider the mechanisms of thermal stresses and the thermal cycling in contact zone, during the gear mesh. This research has been conducted for the first point of contact based on consideration of transient heat transfer, elastohydrodynamic lubrications, and surface roughness and gear material. A procedure presented in this paper evaluating the stresses (thermal and mechanical) and predicting the design criteria for modifying the contact stresses due to thermal stresses. The effect of the material, oil film thickness, surface roughness and geometric operating parameters on modification parameter is illustrated. Also the effects of a load on the temperature rise and the modification parameters are evaluated.
Keywords: Gear tooth surface failure; Thermal stress effect; Transient temperature rise; Gear teeth